Efeito antimetastático e mecanismos de ação de proteases do látex de Vasconcellea cundinamarcensis (Carica candamarcensis) - Dalton Dittz Junior (2011)
The proteolytic fraction P1G10 from Vasconcellea cundinamarcensis latex shows antitumor and/or antimetastatic activity in murine melanoma and Ehrlich carcinoma. The aim of this study was to evaluate the P1G10 sub-fractions, CMS-1 and CMS-2, regarding the antimetastatic effect in murine colon carcinoma (CT26.WT) and melanoma (B16-F10) and its possible mechanisms of action. In colon carcinoma, 1 or 5 mg/kg of P1G10 and 5 mg/kg of CMS-2 showed antimetastatic effect. In melanoma, this effect was observed with 5 mg/kg of CMS-2 and with 5 mg/kg of P1G10, as previous studies by the research group. P1G10 showed cytotoxicity against normal (CHO and BHK-21) and tumor (B16-F10 and CT26.WT) cells, with IC-50 equal or less than 21 g/mL, while CMS-2 had this effect selectively on tumor cells (IC-50 less than 11 g/mL). CMS-2 or P1G10 100 g/mL lead to an increase in the sub-diploid DNA content in cells exposed to different periods. Still, P1G10 exerts this effect by an action dependent on its proteolytic activity and a caspase-dependent pathway. Treatment with P1G10 100 g/mL, 2h, promoted a decrease in tumor cells adhesion to extracellular matrix components and to the invasiveness of these cells. Throughout the study, CMS-1 showed no significant effect. Thus, the proteases contained in CMS-2 are responsible for the antimetastatic action of P1G10 and contributes to this effect the cytotoxicity, through apoptosis and dependent on their proteolytic activities, and also the reduction of cellular adhesion and invasion